2021
DOI: 10.7759/cureus.15307
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Causes of Hyperuricemia in Children

Abstract: IntroductionThere are various factors responsible for hyperuricemia in children, however, there is extremely limited local data available. In this study, we aim to determine the causes and risk factors associated with hyperuricemia. This study will assist pediatric consultants to identify children who might be at risk of hyperuricemia and manage them accordingly. MethodsThis study was conducted in pediatric outpatient departments of various tertiary care hospitals from January 2018 to December 2019. Five thous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Considering that changes in uric acid levels occur gradually during development, it is natural that the amount of uric acid depends on age, as seen in our study. In line with this finding of ours, Kumar and colleagues 2021 showed that hyperuricemia was more common in older children (58).…”
Section: Discussionsupporting
confidence: 84%
“…Considering that changes in uric acid levels occur gradually during development, it is natural that the amount of uric acid depends on age, as seen in our study. In line with this finding of ours, Kumar and colleagues 2021 showed that hyperuricemia was more common in older children (58).…”
Section: Discussionsupporting
confidence: 84%
“…Other studies showed variable results, in a study in Korea 18 the prevalence was ( 9.4%). However, higher results were obtained in the Pakistan study (26.02%) 19 , and in U.S 20 study (30.2%). These differences among studies can be explained as hyperuricemia is the result of combinations of many factors including, genetic, variable lifestyles, and environmental risk factors, in addition to different age group samples among each study.…”
mentioning
confidence: 60%
“…High FPG was defined at ≥ 100 mg/dL 21 and elevated ALT at > 40 IU/L. Hyperuricemia was defined as ≥ 6.0 mg/dL in subjects aged 12 years and ≥ 7.5 mg/dL in subjects aged 13–18 years based on reference values from the Mayo Clinic Laboratories 22 .…”
Section: Methodsmentioning
confidence: 99%